Fracture behavior issues in HSLA pipeline steels - a review - Maleque, M. H. A. Musa; Maleque, Md. Abdul; Ali, Mohammad Yeakub; Hasan, Muhammad Hasibul (Trans Tech Publications, Switzerland, 2015)
The increasing demand for natural gas and oil as an important energy sources has led to rising the application of high strength low alloy steels (HSLA), which indicates continued growth of pipeline installations and the qualification of the actual pipeline network. A difficult problem to be solved for the economic and safe operation of high pressure pipelines is the control of ductile fracture propagation. As a result, the accurate estimation of the resistance to fracture and ductile fracture arrest in pressurized pipelines are important issues. Technology to ensure such control is critical for the structural integrity and safety of pipelines because the possibility of a running fracture opens-up lead to the catastrophic long-running failure of a pipeline which involve public safety and property damage and environment impact. The integrity and high reliability of pipelines depend on various factors including mechanical damage or external interference, fatigue cracks, material defects, weld cracks, improper welding, internal or external corrosion and, most of all, on the ageing of the physical state of the pipeline material and the welded joints during their prolonged use. In order to understand the current problems in the pipeline materials and to develop steels with higher strength, better toughness and weldability, this paper gives brief overview of the comprehensive of fracture behavior including crack initiation and propagation of high strength low alloy pipeline steels.